STRATEGI DESAIN BANGUNAN DI TEPI AIR - Gabi Ayu; Doddy Yuono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2026)
Waterfront areas are strategic urban spaces that are also vulnerable to environmental pressures, such as sea level rise, coastal flooding, and ecosystem degradation. In the architectural discipline, these issues are not only understood as environmental problems, but also as challenges for building design in responding to the dynamic conditions of waterfront areas. This study aims to formulate sustainable building design strategies in waterfront areas through a comparative analysis of international precedent studies. The method used is a qualitative-descriptive approach with precedent studies as the main analytical framework, supported by a review of literature related to Water-Sensitive Urban Design (WSUD), building energy efficiency, and coastal resilience. The two precedents studied, namely Darling Harbour in Sydney and Marina Bay District in Singapore, are positioned as architectural precedents, not environmental case studies, so the focus of the analysis is directed at the relationship between environmental systems and building design decisions. The novelty of this study lies in the development of an architectural analysis framework that explicitly separates the environmental dimensions and the building design dimensions in reading waterfront precedents, so that they can be used as a basis for formulating sustainable building design strategies in waterfront areas. Keywords: Architecture; coastal; energy; water-sensitive urban design waterfront; waterfront Abstrak Kawasan tepi air merupakan ruang perkotaan strategis yang sekaligus rentan terhadap tekanan lingkungan, seperti kenaikan muka air laut, banjir pesisir, dan degradasi ekosistem. Dalam disiplin arsitektur, isu tersebut tidak hanya dipahami sebagai permasalahan lingkungan, tetapi juga sebagai tantangan desain bangunan dalam merespons kondisi dinamis kawasan waterfront. Penelitian ini bertujuan merumuskan strategi desain bangunan berkelanjutan di kawasan tepi air melalui analisis komparatif studi preseden internasional. Metode yang digunakan adalah pendekatan kualitatif-deskriptif dengan studi preseden sebagai kerangka analisis utama, didukung kajian literatur terkait Water-Sensitive Urban Design (WSUD), efisiensi energi bangunan, dan ketahanan pesisir. Dua preseden yang dikaji, yaitu Darling Harbour di Sydney dan Marina Bay District di Singapura, diposisikan sebagai preseden arsitektural, bukan studi kasus lingkungan, sehingga fokus analisis diarahkan pada hubungan antara sistem lingkungan dan keputusan desain bangunan. Kebaruan penelitian ini terletak pada penyusunan kerangka analisis arsitektural yang secara eksplisit memisahkan dimensi lingkungan dan dimensi desain bangunan dalam pembacaan preseden waterfront, sehingga dapat digunakan sebagai dasar perumusan strategi desain bangunan berkelanjutan di kawasan tepi air.